Passivity‐based power control of a doubly fed induction generator with unknown parameters. (14th April 2016) - López‐García, I.; Beltran‐Carbajal, F.; Espinosa‐Pérez, G.; Escarela‐Perez, R.
Summary: An alternative solution for power regulation of doubly fed induction generators is proposed in this work by a proper combination of passivity‐based controllers with algebraic approaches for online estimation of system parameters and mechanical torque. Our proposal shows that the stability property of the original closed‐loop system is preserved, without the restriction of explicitly knowing the parameters and mechanical torque of the induction generator. A performance evaluation study is performed on the passivity‐based power control scheme considering typical/normal operation conditions for the electrical power generation system, namely active power generation with either demanded or delivered reactive power. Analytical and numerical results prove the effectiveness of the power control scheme combined with the proposed real‐time estimators of parameters and torque. Copyright © 2016 John Wiley & Sons, Ltd.